Development and Validation of a Creative Thinking Skills Test Instrument Based on the 4D Model (Define-Design-Develop) for High School Students on Static Fluid Material - Dya Atul Fahmi; Parno Parno; Khusaini Khusaini; Marlina Ali (Universitas Lambung Mangkurat, 2026)
Creative thinking skills are an important 21st-century competency in physics learning, but currently, the availability of test instruments specifically measuring these skills in static fluids is still limited and has not fully met the criteria for validity and reliability. This study aims to develop a valid, reliable, and suitable instrument for testing creative thinking skills in static fluids for high school students. The study uses a 4D development model through the define, design, and develop stages. The implementation stage has just reached 3D. This instrument was designed based on indicators of fluency, flexibility, originality, and elaboration. Internal validation was conducted by two expert lecturers, while external validation was conducted through a trial on 70 high school students who had previously studied static fluids. The results of the internal analysis showed that all test items were categorized as very valid with an average validity percentage of 88.67% and a range of 81.25%–93.75%. Meanwhile, the results of the external analysis showed that the instrument was empirically valid with an item-total correlation coefficient ranging from 0.498 to 0.762; reliable with a Cronbach's Alpha value of 0.797; had a dominant difficulty level in the medium category with a difficulty index ranging from 0.35 to 0.79; and had moderate-to-very-high discrimination power with a discrimination index ranging from 0.336 to 0.617. Thus, the developed instrument is suitable for use as an assessment tool to measure creative thinking skills in static fluids in high school students. The implication of this research is the availability of instruments that can support improving the quality of physics learning evaluation and become a reference for teachers and researchers in developing assessments of high-level thinking skills.